Counterfeit : a novel - Chen, Kirstin, 1981- (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
Ava Wong, a strait-laced Chinese American lawyer, and Winnie Fang, her former college roommate from mainland China, who dropped out under mysterious circumstances, join forces in an ingenious counterfeit operation selling replica luxury handbags.
Keywords: Chinese American women -- Fiction; Female friendships -- Fiction; Counterfeits and founterfeiting -- Fiction; International trade -- Fiction; Product counterfeiting -- Fiction; Handbags -- Fiction; Women-owned business enterprises -- Fiction; Domestic fiction; Thrillers (Fiction)